Teachers' Contributions to School Improvement Reflections on Fifteen Years of Research. R&D Report 3219 - Rutherford, William L.; Texas Univ., Austin. Research and Development Center for Teacher Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
A report is given on findings of research studies on how teachers respond to attempts to implement educational innovations. In many cases, teachers believe their future in relation to the innovation is determined not by them, but by some superordinate. Other teacher responses may be the conviction that the change will soon fade away as other fads have or questioning the value of the change. Some teachers may also give the impression that they are using an innovation when, in fact, they are not. Researchers have concluded that teachers are most often the recipients rather than the initiators of any change affecting their classrooms and are therefore resistant to innovations. It is pointed out that although it is essential that teachers be receptive to change, when large numbers of participants are involved (as in a district-wide program), developing universal teacher ownership of the change is not possible. The effectiveness of the Concerns-Based Adoption Model (CBAM) in facilitating implementation of an innovation is discussed. The CBAM is a systematic plan for facilitating change that gives teachers priority consideration. (JD)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (70th, San Francisco, CA, April 16-20, 1986).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Change Agents; Educational Change; Educational Innovation; Locus of Control; Program Implementation; Teacher Influence; Teacher Participation; Teacher Response; Teacher Role; Concerns Based Adoption Model; Speeches/Meeting Papers; Reports, Descriptive